ENHANCING STUDENTSâ COGNITIVE ABILITIES THROUGH STUDENTS-CENTERED LEARNING (SCL) - Amri, Faisal; Ekaningsih, Nur (Kajian Linguistik dan Sastra, 2017)
AbstractThis conceptual paper, presents about the result of discussion regarding students-centered learning improves studentsâ cognitive ability. SCL improves skillsÂ  byÂ  developingÂ  cognitiveÂ  abilityÂ  liesÂ  withinÂ  themÂ  asÂ  theÂ  firstÂ  basicÂ  skill. It is important for students to have adequate cognitive abilities to keep up the materials which are being taught by teachers. Therefore, this paper will explain about cognitive ability. Cognitive ability which is affecting on learning process, has made some teachers struggle to seek a way how to improve it. There are few methods that have been chosen thoroughly for developing cognitive abilities on students. First is about developing thinking that refers mainly to how students think effectively and creatively. Second is about cooperative learning that refers to how students cooperate or work with other and effect of partners in learning process. Third is about learnersâresponsibility that has correlation with studentsâ responsible which affects on objectives of learning.Â Keywords: Students-Centered Learning, Cognitive Ability, Developing ThinkingSkill, Cooperative Learning, LearnersâResponsibility.